2015
DOI: 10.1002/mrd.22478
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates inflammation and oxidative stress in epididymal white adipose tissue: Implications for its involvement in improving steroidogenesis in diet‐induced obese mice

Abstract: Chronic, low-grade systemic inflammation has been shown to play an important role in the development of obesity-related complications. Epididymal white adipose tissue (WAT) can influence testicular function through its endocrine function. The purpose of this study was to assess the effects of resveratrol on the epididymal WAT inflammatory response and on testicular steroidogenesis in obese individuals. Seven-week-old male C57BL/6J mice were fed a high-calorie and high-cholesterol diet (HCD group) or HCD supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 33 publications
(52 reference statements)
1
17
0
Order By: Relevance
“…Other authors have focused on the capacity of pure polyphenols and polyphenol-rich extracts to modulate adipocyte hypertrophy, but not hyperplasia, in rodent models of diet-induced obesity. For example, polyphenol-rich grape pomace, 25 resveratrol 26 or piceatannol 27 supplementation reduces epididymal adipocyte size. Moreover, consistent with our results, long-term resveratrol supplementation reduces adipocyte size in visceral, but not subcutaneous, WAT in rhesus monkeys fed a high-fat, high-sugar diet.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have focused on the capacity of pure polyphenols and polyphenol-rich extracts to modulate adipocyte hypertrophy, but not hyperplasia, in rodent models of diet-induced obesity. For example, polyphenol-rich grape pomace, 25 resveratrol 26 or piceatannol 27 supplementation reduces epididymal adipocyte size. Moreover, consistent with our results, long-term resveratrol supplementation reduces adipocyte size in visceral, but not subcutaneous, WAT in rhesus monkeys fed a high-fat, high-sugar diet.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of immunohistochemistry was followed as the described 52 , but with minor modification, in which the hepatic sections were developed with a DAB kit (Fuzhou Maixin Biotech. Co., Ltd., Fuzhou, China) and the nuclei were stained by hematoxylin.…”
Section: Methodsmentioning
confidence: 99%
“…Resveratrol also showed antioxidant effect in animal models. Lv et al found that resveratrol attenuated diet-induced oxidative stress in epididymal white adipose tissue partly by the reduction of Sirt1 and manganese superoxide dismutase (Sod2) levels [ 99 ].…”
Section: Resveratrolmentioning
confidence: 99%